PERBEDAAN ZONA HAMBAT PERTUMBUHAN Staphylococcus aureus PADA BERBAGAI KONSENTRASI REBUSAN DAUN SALAM (Syzygium polyanthum) SECARA IN VITRO - nyoman mastra (Jurusan Analisis Kesehatan, Poltekkes Kemenkes Denpasar, 2017)
AbstractBackground Staphylococcus aureus is one of causes infection and this bacteria have been resistence for many antibiotic. Bay leaf have antibacterials substance, which stew leaves can be treat infection caused Staphylococcus aureus. The purpose of this study was to determine differences in growth inhibition zone of Staphylococcus aureus at various concentrations of water stew of bay leaf.Method The method of this study is true experiment with posstest only control design, and used Kirby Bauer disk diffusion method with various concentrations of water stewed of bay leaf (20%, 40%, 60%, 80%,100%), positive control (chloramfenicol 30 μg) and negative control (sterile distilled water). Result The result showed that the average diameter of inhibition zone in concentration 20%, 40%, 60%, 80%, and 100% is 7 mm, 8,4 mm, 9,6 mm, 10,5 mm and 11,5 mm. Based on statistical analysis using oneway ANOVA available the value of p (0,000) α (0,05), so the inhibition zone is significant difference of growth inhibition zone of Staphylococcus aureus at various concentrations of stewed water bay leaf. Conclusion Water stew of bay leaf can inhibit the growth of Staphylococcus aureus, and there are differences in growth inhibition zone of Staphylococcus aureus at various concentrations of water stew of bay leaf. Keywords: stew of bay leaf; Staphylococcus aureus; inhibition zone